The Relationship Between Subjective Well Being And Narcissistic Behavior In Students Using Instagram On Campus: Hubungan Antara Subjective Well Being Dengan Perilaku Narsistik Pada Mahasiswa Pengguna Instagram di Kampus - Arum Trissandy; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the phenomenon of students experiencing narcissistic behavior. This study aims to determine the relationship between subjective well being and narcissistic behavior in students using Instagram at the University of Muhammadiyah Sidoarjo. This research is a type of quantitative research with a correlational approach. The population in this study were all students of the University of Muhammadiyah Sidoarjo, totaling 10,806 students. The sample in this study were 340 students using probability sampling and random sampling. Data collection techniques in this study used a subjective well being scale (ɑ = 0.949) and a narcissistic behavior scale (ɑ = 0.951). The data analysis technique used Pearson's product-moment correlation with the help of SPSS 18.0. The results of this research data analysis indicate that the correlation coefficient (rxy) is -0.535 with a significance of 0.000 <0.05, which means that there is a significant negative relationship between subjective well-being and narcissistic behavior in students using Instagram at the University of Muhammadiyah Sidoarjo. The effect of subjective well being on narcissistic behavior in this study was 28.6%.